2019
DOI: 10.5194/bg-16-2837-2019
|View full text |Cite
|
Sign up to set email alerts
|

Reviews and syntheses: Insights into deep-sea food webs and global environmental gradients revealed by stable isotope (<i>δ</i><sup>15</sup>N, <i>δ</i><sup>13</sup>C) and fatty acid trophic biomarkers

Abstract: Abstract. Biochemical markers developed initially for food-web studies of terrestrial and shallow-water environments have only recently been applied to deep-sea ecosystems (i.e., in the early 2000s). For the first time since their implementation, this review took a close look at the existing literature in the field of deep-sea trophic ecology to synthesize current knowledge. Furthermore, it provided an opportunity for a preliminary analysis of global geographic (i.e., latitudinal, along a depth gradient) trend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 108 publications
1
10
0
Order By: Relevance
“…Biochemical techniques such as fatty acid and stable isotope analyses have become widely-used approaches to complement GCA in ecological studies (Nielsen et al 2018;Parzanini et al 2019). Stable isotope values can provide trophic position estimates of siphonophores, and information about the trophic structure of zooplankton communities independent of GCA.…”
Section: Methodological Advancements In Siphonophore Collection and D...mentioning
confidence: 99%
“…Biochemical techniques such as fatty acid and stable isotope analyses have become widely-used approaches to complement GCA in ecological studies (Nielsen et al 2018;Parzanini et al 2019). Stable isotope values can provide trophic position estimates of siphonophores, and information about the trophic structure of zooplankton communities independent of GCA.…”
Section: Methodological Advancements In Siphonophore Collection and D...mentioning
confidence: 99%
“…POM from our collection localities are not available. Globally, average deep-sea heterotrophic animals have isotopic values ranging from 10-13 for δ 15 N and −17 to −21 for δ 13 C, depending on latitude (reviewed in Parzanini et al, 2019). POM data from the literature show elevated values compared with nitrogen fixed by bacteria.…”
Section: Taxonmentioning
confidence: 99%
“…Deep-sea nitrogen particulates may have comparatively high δ 15 N signatures (Sigman and Casciotti, 2001). Globally, deep-sea heterotrophic animals have average δ 15 N isotopic values from 10 to 13 depending on latitude (reviewed in Parzanini et al, 2019). Montoya et al (2002) found POM δ 15 N increases rapidly to 6-8 in the first 300 m in the tropical Atlantic.…”
Section: Clade Membership and Preservation Effectsmentioning
confidence: 99%
“…Fatty acids can provide complementary information on deep-sea food web functioning (Colaço et al, 2007;Parzanini et al, 2019), particularly for unravelling the transfer of organic matter from sponges to the wider food web. Sponges contain specific fatty acids that can serve as a biomarker, like mid-chain-branched fatty acids containing single methyl groups between the ω5 and ω9 positions, which are unique microbial markers of the associated microbiota of sponges that are typically not found in the environment ( de Kluijver, Nierop, et al, 2021;Thiel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Compound‐specific‐isotope analyses of amino acids can be used to unravel trophic positions and food web interactions based on differential fractionation of amino acid nitrogen isotopes from food source to consumer (Chikaraishi et al, 2009; McClelland & Montoya, 2002). Fatty acids can provide complementary information on deep‐sea food web functioning (Colaço et al, 2007; Parzanini et al, 2019), particularly for unravelling the transfer of organic matter from sponges to the wider food web. Sponges contain specific fatty acids that can serve as a biomarker, like mid‐chain‐branched fatty acids containing single methyl groups between the ω5 and ω9 positions, which are unique microbial markers of the associated microbiota of sponges that are typically not found in the environment (de Kluijver, Nierop, et al, 2021; Thiel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%